2019
DOI: 10.1007/s13167-019-00168-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomogram estimating post-surgery hospital stay of lung cancer patients: relevance for predictive, preventive, and personalized healthcare strategies

Abstract: Objective In the era of fast track surgery, early and accurately estimating whether postoperative length of stay (p-LOS) will be prolonged after lung cancer surgery is very important, both for patient's discharge planning and hospital bed management. Pulmonary function tests (PFTs) are very valuable routine examinations which should not be underutilized before lung cancer surgery. Thus, this study aimed to establish an accurate but simple prediction tool, based on PFTs, for achieving a personalized prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
9
0
1
Order By: Relevance
“…The anchor (PPCs) we used significantly correlated with postoperative length of stay, which is commonly used in oncology practice for reflecting surgical skill and quality of care. 55 Development of any PPCs, even if mild, is associated with reduced survival, prolonged stay in the hospital and increased in-hospital mortality. 56 Additionally, our analysis demonstrated that the CP6-defined severe SOB level was associated with higher MDASI-LC symptom interference levels, suggesting that CP6 can be interpreted for functional impairment, similar as the pain and fatigue cutpoints anchored on the MDASI symptom interference.…”
Section: Discussionmentioning
confidence: 99%
“…The anchor (PPCs) we used significantly correlated with postoperative length of stay, which is commonly used in oncology practice for reflecting surgical skill and quality of care. 55 Development of any PPCs, even if mild, is associated with reduced survival, prolonged stay in the hospital and increased in-hospital mortality. 56 Additionally, our analysis demonstrated that the CP6-defined severe SOB level was associated with higher MDASI-LC symptom interference levels, suggesting that CP6 can be interpreted for functional impairment, similar as the pain and fatigue cutpoints anchored on the MDASI symptom interference.…”
Section: Discussionmentioning
confidence: 99%
“…The innovative PPPM is emerging as the hotspot of efforts in healthcare aimed at curbing the prevalence of chronic diseases such as cardiovascular diseases, diabetes and cancer [ 28 , 51 , 52 ]. PPPM concepts have actually been practically applied to cardiovascular diseases, diabetes, oral medicine, chronic diseases, as well as tumor therapy and tumor postoperative evaluation [ 2 , 53 55 ]. But the study of SHS and PS related factors among nurses in English literature was not searched.…”
Section: Discussionmentioning
confidence: 99%
“…LOS was calculated from the date of admission to the date of checkout. A LOS exceeding the third quartile value of the study population was defined as prolonged LOS [17][18][19][20][21][22]. Specifically, hospitalization < 13 days was defined as normal LOS; whereas, hospitalization ≥ 14 days was defined as prolonged LOS.…”
Section: Definitionmentioning
confidence: 99%